PROSPEK KOMERSIALISASI PRODUK MIKROBA DI BIDANG PERTANIA - PRIHASTUTI, PRIHASTUTI (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
A microbial product commercialized is the final of a series of integrated research. This project started from a laboratory research, semi-field (greenhouse) into the field, to scale factories. The research procedures must be achieved, to maintain the quality of the microbial products. This paper raised the status and prospects for a microbial product commercialized in agriculture that can be developed and marketed, including the microbe that are active in the supply of nutrients, producing a substance in promoting plant growth and pest control. Technology of microbial commercialized covers: discovery, microbial strain development, greenhouse and field testing, formulation and implementation of products, regulatory, consumer response and market share. An economical aspect of soil microbial technology is determined by reference to the identification and quantification of financial research, processing time require, price of product, market share and return on investment.